Roles played by civil society organisations in supporting homeless people with health care-seeking and accessing the social determinants of health in Delhi, India: Perspectives of support providers and receivers - Devaki Nambiar; Bincy Mathew (SSM: Qualitative Research in Health, 2022)
Civil Society Organisations (CSO) have played a significant role globally in improving access of under-served populations to healthcare, including the homeless. In India, while there exist small-scale initiatives such as night shelters and recovery shelters run by the urban local government in coordination with CSOs to support homeless people, evidence on how these services function and are experienced is lacking. This analysis sought to describe the roles played by CSOs – alone and in partnership with the government – as well as how these were experienced by homeless people. A qualitative study consisting of five Focus Group Discussions, 24 In Depth Interviews, and non-participant observation was carried out among homeless people staying in shelters and the streets in India's national capital, Delhi. Data analysis was done using a grounded theory approach with inductive generation of themes. CSOs provided various forms of support - ranging from the provision of night shelters for temporary accommodation, recovery shelters for ailing homeless people requiring support and provisional accommodation for convalescence, drinking water and sanitation, to basic health services, first aid treatment, diagnostic tests, mental health counselling, support with treatment costs, and patient navigation. Notwithstanding constraints of funding and networks that hampered continuity and comprehensiveness of care, CSOs are key in ensuring access to health services and social determinants among the urban poor; their impact and the possibility of networking and scaling up their efforts warrant further study.